What Is Nonacid Reflux Disease? - Martin A Storr (Canadian Journal of Gastroenterology)
Proton pump inhibitors (PPIs) are the gold standard treatment for gastroesophageal reflux disease. In clinical practice, failure of PPIs occurs frequently, and may affect up to 30% of patients in a typical gastroenterology practice. Multichannel impedance monitoring combined with pH monitoring helps to detect nonacid reflux, and if symptoms correlate with these nonacid reflux episodes, nonacid reflux disease can be diagnosed. In contrast to PPIs, reflux inhibitors target transient lower esophageal sphincter relaxations, which are involved in the pathophysiology of reflux disease and may be the appropriate future treatment for nonacid reflux disease. The present article discusses the current understanding of nonacid reflux disease, its diagnosis and treatment.